A Comparison of the Water Absorption and Water Solubility Values of Four Different Composite Resin Materials - Faruk Öztekin; Samet Tekin; Özkan Adıgüzel; Suzan Cangül; Ömer Satıcı (Cumhuriyet University, 2018)
Objectives: The aim of this study was to compare the water absorption and water solubility of four different composte resin materials. Materials and methods: A total of 40 cylindrical discs were prepared and polymerised with light, as 10 from each group, each sample 2mm in depth and 8mm in diameter. The samples were kept for 24 hrs in a dessicator until a stable weight was reached. Then, the weight of each sample was measured on highly sensitive scales. To calculate the water absorption and solubility, measurements were made again with the sensitive scales at the end of 1, 7 and 30 days. The data obtained were evaluated with One-Way ANOVA variance analysis and the Friedman test. Results: As a result of the statistical analyses, significant differences were determined between the composite resins in respect of water absorption on days 7 and 30 and in respect of solubility on day 30 only. Conclusions: It can be concluded that the negative mechanical, physical and biological effects created by the water absorption and water solubility factors of restorative materials are important issues that should be taken into consideration.